Robust and Long-Lasting Immunity and Protection in Mice Induced by Lipopolyplex-Delivered mRNA Vaccines Expressing the Prefusion Protein of Respiratory Syncytial Virus - Xuchang Shan; Ruiwen Han; Xueting Cheng; Jialuo Bing; Zhenyong Qi; Shucai Sun; Tangqi Wang; Qiaohong Chu; Yao Deng; Desheng Zhai; Wenjie Tan (Vaccines)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in infants and children. mRNA vaccines based on the lipopolyplex (LPP) platform have been previously reported, but they remain unapplied in RSV vaccine development. In this study, we developed a novel LPP-delivered mRNA vaccine that expresses the respiratory syncytial virus prefusion protein (RSV pre-F) to evaluate its immunogenicity and protective effect in a mouse model. We synthesized mRNAs with gene modification for RSV pre-F and prepared mRNA vaccines using the LPP delivery platform, referred to as RSV pre-F LPP-mRNA. RSV pre-F protein expression in mRNA vaccines was characterized in vitro. Then, we evaluated the effects of the immune response and protection of this mRNA vaccine in mice up to 24 weeks post-vaccination. Following booster immunization, robust and long-lasting RSV pre-F-specific IgG antibodies were detected in the serum of mice, which exhibited Th1/Th2 balanced IgG response and cross-neutralizing antibodies against different subtypes (RSV A2, B18537, and clinical isolate hRSV/C-Tan/BJ 202301), with a clear dose–response relationship observed. RSV pre-F-specific IgG antibodies were maintained in the mice for an extended period, lasting up to 18 weeks post-immunization. Concurrently, multifunctional RSV F-specific CD8+ T cells (IFN–γ, IL-2, and TNF-α) were detected in the mice. After RSV A2 challenge, the RSV pre-F LPP-mRNA vaccine led to a significant reduction in viral replication, while reduced pathological damage was observed in lung tissue. The LPP-delivered mRNA vaccine expressing RSV pre-F induces a robust and long-lasting immune response and protection, indicating good prospects for further development and application.